Association between biomass fuel use and the risk of cognitive impairment among older populations in China: a population-based cohort study - Min Du; Liyuan Tao; Lin Zhu; Jue Liu (Environmental Health, 2021)
Abstract Background Cohort studies on the impact of biomass fuel use for cooking on cognitive impairment among older population are still lacking in China and elsewhere. The aim of this study was to examine whether biomass fuel use for cooking is associated with cognitive impairment in Chinese adults aged 65 years or older. Methods The prospective population-based cohort study of the Chinese Longitudinal Healthy Longevity Survey (CLHLS) included participants aged 65 years or older in 2014 who were followed-up until 2018 in 23 provinces in China. The Mini-Mental State Examination (MMSE) was used to assess cognitive function, and cognitive impairment was defined as total MMSE scores less than 18. The association between biomass fuel use and cognitive impairment was evaluated using the Cox proportional hazards model. Results Of the 4145 participants included at baseline, participants who reported that they used biomass fuel for cooking (40.43%; IR: 3.11 versus 2.77 per 100 person-years; aHR: 1.27, 95% CI: 1.02–1.58) had a higher risk of cognitive impairment compared with participants who used clean fuels (53.75%). A stratified analyses showed greater effect estimates of cognitive impairment in the older people that lived in the rural areas (aHR: 1.444, 95% CI: 1.08–3.90) and never smoked (aHR: 1.33, 95% CI: 1.04–1.71). Conclusions These findings demonstrated that biomass fuel used for cooking was associated with cognitive impairment, as defined by MMSE, in a population-based study of elderly in China. To prevent cognitive impairment, the structure of cooking fuels requires improvements.